2014
DOI: 10.1097/qad.0000000000000109
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the population-level impact of antiretroviral treatment

Abstract: The relative and absolute benefit of ART expansion depends on baseline condom use, ART coverage, and epidemic size. In south India, maximizing FSWs' access to care, followed by maximizing clients' access are the most efficient ways to expand ART for HIV prevention, across baseline intervention context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The best implementation strategies for specialized HIV-positive communities and their larger population in which they reside should also be investigated and employed to ensure the success of TasP. For instance, it was found that prioritizing access to care to female sex workers and their clients was the most efficient way to expand ART and avert remaining HIV infections within the general population in a ten year period in South India, rather than expanding ART eligibility (Mishra, Mountain, Pickles, Vickerman, Shastri, Gilks et al, 2014).…”
Section: ) Prioritized Tasp Scale-up In Key Populations At High Riskmentioning
confidence: 99%
“…The best implementation strategies for specialized HIV-positive communities and their larger population in which they reside should also be investigated and employed to ensure the success of TasP. For instance, it was found that prioritizing access to care to female sex workers and their clients was the most efficient way to expand ART and avert remaining HIV infections within the general population in a ten year period in South India, rather than expanding ART eligibility (Mishra, Mountain, Pickles, Vickerman, Shastri, Gilks et al, 2014).…”
Section: ) Prioritized Tasp Scale-up In Key Populations At High Riskmentioning
confidence: 99%
“…Models constructed around concentrated epidemics in Asia have found that the relative benefits of ART expansion in FSW are highly dependent on condom use and epidemic size. 24,25 Few models have been constructed around FSW in West Africa, where successful targeted interventions have been in place since the 1990s, which could influence gains of ART expansion. 26,27 Burkina Faso is one of several nations in which the incidence of HIV has declined, despite limited availability of ART until recently.…”
Section: Introductionmentioning
confidence: 99%
“…171 A recent modeling study in India suggests that in the presence of existing condom-based interventions, existing ART programs could avert 11-28% of the remaining HIV infections in FSW between 2014 and 2024. 172 Several studies of TasP are ongoing in India, Vietnam, Thailand, China, and Indonesia. In China, a 10-fold increase in ART could decrease the number of HIV-related deaths by 58% and the number of new infections by 25% by 2015.…”
Section: Treatment As Prevention (Tasp)mentioning
confidence: 99%